Analysis of Multiple Families With Single Individuals Affected by Pseudohypoparathyroidism Type Ib (PHP1B) Reveals Only One Novel Maternally Inherited GNAS Deletion. (14th November 2015) - Takatani, Rieko; Molinaro, Angelo; Grigelioniene, Giedre; Tafaj, Olta; Watanabe, Tomoyuki; Reyes, Monica; Sharma, Amita; Singhal, Vibha; Raymond, F Lucy; Linglart, Agnès; Jüppner, Harald
ABSTRACT: Proximal tubular resistance to parathyroid hormone (PTH) resulting in hypocalcemia and hyperphosphatemia are preeminent abnormalities in pseudohypoparathyroidism type Ib (PHP1B), but resistance toward other hormones as well as variable features of Albright's Hereditary Osteodystrophy (AHO) can occur also. Genomic DNA from PHP1B patients shows epigenetic changes at one or multiple differentially methylated regions (DMRs) within GNAS, the gene encoding Gαs and splice variants thereof. In the autosomal dominant disease variant, these methylation abnormalities are caused by deletions in STX16 or GNAS on the maternal allele. The molecular defect(s) leading to sporadic PHP1B (sporPHP1B) remains in most cases unknown and we therefore analyzed 60 sporPHP1B patients and available family members by microsatellite markers, single nucleotide polymorphisms (SNPs), multiplex ligation‐dependent probe amplification (MLPA), and methylation‐specific MLPA (MS‐MLPA). All investigated cases revealed broad GNAS methylation changes, but no evidence for inheritance of two paternal chromosome 20q alleles. Some patients with partial epigenetic modifications in DNA from peripheral blood cells showed more complete GNAS methylation changes when testing their immortalized lymphoblastoid cells. Analysis of siblings and children of sporPHP1B patients provided no evidence for an abnormal mineral ion regulation and no changes in GNAS methylation. Only one patient revealed, based on MLPA and microsatellite analyses, evidence for an allelic loss, which resulted in the discovery of two adjacent, maternally inherited deletions (37, 597 and 1427 bp, respectively) that remove the area between GNAS antisense exons 3 and 5, including exon NESP. Our findings thus emphasize that the region comprising antisense exons 3 and 4 is required for establishing all maternal GNAS methylation imprints. The genetic defect(s) leading in sporPHP1B to epigenetic GNAS changes and thus PTH‐resistance remains unknown, but it seems unlikely that this disease variant is caused by heterozygous inherited or de novo mutations involving GNAS . © 2015 American Society for Bone and Mineral Research.